2006
DOI: 10.1542/peds.2006-0900iiii
|View full text |Cite
|
Sign up to set email alerts
|

Missed Opportunities for Influenza Vaccination in Children With Chronic Medical Conditions

Abstract: PURPOSE OF THE STUDY. To assess the frequency and characteristics of missed opportunities for influenza immunization in children with chronic medical conditions, and among unimmunized children in that group, to explore parent-reported reasons for not vaccinating their child. STUDY POPULATION. A cohort of 926 children (aged 6 to 72 months) who were identified from October 1, 2002, through January 31, 2003, as having Ն1 high-risk conditions (HRCs). A total of 594 (64%) were male, and 734 (79%) were between 24 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 1 publication
3
18
0
Order By: Relevance
“…Others have reported that lack of physician recommendation was related to lower immunization rates. 10 These results suggest a need for new approaches. The Task Force on Community Preventive Services 15 suggests interventions at all levels to improve immunization rates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have reported that lack of physician recommendation was related to lower immunization rates. 10 These results suggest a need for new approaches. The Task Force on Community Preventive Services 15 suggests interventions at all levels to improve immunization rates.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in children with asthma seen in primary care settings, influenza vaccination rates increased from 7-10 to 30-42% with patient reminders/recall. 5,[7][8][9][10] In the emergency department, education combined with offering vaccination increased rates to 57% compared with 36% for education only. 11 Although few studies have specifically addressed parental barriers to and facilitators of influenza vaccination of children with chronic medical conditions, one study reported that parents believed that children received too many immunizations, that immunizations can weaken the immune system and that influenza vaccine causes illness.…”
Section: Introductionmentioning
confidence: 99%
“…In a cohort study of an infant population with associated conditions (n Z 926), 78% of visits by asthmatic children and 74% of those by children with other associated conditions were counted as wasted opportunities for vaccination. 44 Paediatricians play an essential role in improving vaccination coverage in the infant population at risk. In Spain the influenza vaccine is administered free of charge at the primary care centres, paediatricians attending high-risk children are therefore responsible for recommending the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show that primary care paediatricians may have an insufficient knowledge about the recommendations; effectiveness and safety of influenza vaccine and as a consequence do not vaccinate their high-risk patients. 12,44,45 We consider necessary to urgently implement interventions aimed at increasing parents' and paediatricians' awareness of the importance of influenza and knowledge of the excellent safety, tolerability and effectiveness of influenza vaccines. 45 Other strategies that have proven their efficacy at increasing vaccination coverage, and should be considered are the following: influenza vaccination in the official vaccination schedule, telephoning or mailing personal reminders to high-risk patients, compliance monitoring, using computerized systems to identify high-risk patients and empowering nurses to vaccinate patients directly.…”
Section: Discussionmentioning
confidence: 99%
“…94 For pediatric immunizations, examples of T3 research include studies in multiple practices-under less controlled environments-designed to evaluate interventions such as patient reminder/recall, provider prompts, or interventions to reduce missed opportunities for vaccinations. [95][96][97] For pediatric asthma, examples include studies in multiple practices to educate primary care providers about guideline-based asthma care to optimize management. 98,99 T4 translational research (population-based) involves outcomes assessments at the community or population (public health) level.…”
Section: An Expanded Definitionmentioning
confidence: 99%